Analysis of Financial Statements to Assess Financial Performance: Empirical Study of PT. Unilever Indonesia Tbk - Nawawi, N. (Manunggal Halim Jaya, 2025)
This study aims to analyze the financial performance of PT Unilever Indonesia Tbk during the 2020–2023 period by using a financial ratio analysis method which includes liquidity ratio, solvency, activity, and profitability. The data used is secondary data from the company's annual financial statements. The analysis method applied is horizontal analysis to compare financial performance between periods. The results of the study show that the liquidity ratio tends to decrease, indicating that the company's ability to meet short-term obligations is decreasing. Solvency ratios are increasing, indicating an increased reliance on external financing that can increase financial risks. The activity ratio shows fluctuating efficiency in asset use and receivables management, while the profitability ratio decreases consistently, reflecting a decrease in the company's efficiency in generating profits.